Проблематика кібербезпеки в пристроях FPGA - Мітрофанов, С. В.; Білоцерківець, О. Г. (ХНУРЕ, 2024)
This article navigates the intricate terrain of FPGA cybersecurity, delineating the challenges posed by their hybrid nature and the evolving threat landscape. Exploring various attack vectors—from active disruptions to passive data extraction-it underscores the imperative for a multi-layered defense strategy. With insights into defense mechanisms, including dynamic adaptation and post-quantum preparedness, the article advocates for proactive measures to fortify FPGA-based systems against emerging cyber threats.
Keywords: FPGA; Кібербезпека